Transitioning from Academia to Workforce: Addressing the Challenges Faced by University Graduates in Securing Employments in the Labor Market - Sikubwabo , Dr. Cyprien; Rukundo , Desire; Ruhumuriza, Gaspard; Mukunzi , Desire (African Journal of Education,Science and Technology (AJEST), 2024)
This study investigated the challenges faced by university graduates in Rwanda as they transition from academia to the workforce, with a focus on securing employment in diverse industries and sectors. The objectives were to explore these challenges and identify strategies that higher education institutions can adopt to better prepare their graduates for professional environments. Using purposive sampling, 30 unemployed graduates, 20 human resource managers, and 15 educators were selected for in-depth interviews. Thematic analysis was employed to analyze qualitative data gathered from these interviews, revealing recurring patterns, underlying meanings, and significant themes. The findings highlight various obstacles encountered by graduates, including skill mismatch, limited networking, inadequate guidance, and a competitive job market. A notable issue is the misalignment between academic qualifications and industry needs, exacerbating skill mismatch. To address these challenges, collaboration between academia, industry, and policymakers is crucial, alongside strategies such as integrating practical training, fostering industry collaboration, and emphasizing digital literacy and soft skills development. Recommendations also include curriculum review and adaptation, entrepreneurship education, and the establishment of continuous feedback mechanisms. Internship and apprenticeship opportunities are emphasized as essential for providing hands-on experiences. Implementing these strategies can enhance graduates’ practical readiness and contribute to their employability, fostering a seamless transition into professional environments while promoting individual success and economic development in Rwanda.